До питання про комунікативну поведінку егоїста - Мельник, Олена; Melnyk, Olena (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто поняття комунікативної особистості як зміст, центр і єдність комунікативних актів, спрямованих на інші комунікативні особистості. Акцентовано увагу на основні типи комунікативної особистості, такі як домінантний, мобільний, ригідний, інтровертний. Окреслено комунікативно-мовленнєвий стиль як характерний патерн мовленнєвої поведінки, який реалізує одну з комунікативних стратегій, властиву індивідууму, різним соціальним групам, національно-культурним спільнотам. Проаналізовано риси англійської й американської комунікативної поведінки. Виділено параметри комунікативної поведінки для опису комунікативної поведінки егоїста: комунікативна самопрезентація, комунікативний тиск, комунікативна потреба в інформації, комунікативний самоконтроль, невербальна організація спілкування, комунікативний стиль.The article deals with the notion of communicative personality that presupposes the content of the message, the element or elements which are at the centre of it, and the unity of the communicative acts which are focused on other communicative personalities. Attention is focused on the main types of communicative personalities, such as dominant, mobile, rigid and introspective. The communicative-speech style was characterized as the distinctive pattern of speech behaviour that realizes one of the communicative strategies which are appropriate for individuals, for various social groups and for national and cultural communities. American and British communicative behaviour patterns have been analyzed, in view of the fact that all traits of national character and mentality have an influence on communication. The parameters of communicative behaviour relevant to the description of the communicative behaviour of egotists have been indicated; they include aspects such as communicative self-presentation, communicative pressure, the communicative need for information, communicative self-control, the nonverbal organization of communication and communicative style.
To the Problem of Communicative Behavior of an Egotist.
Keywords: комунікативна особистість; комунікативна поведінка; комунікант-егоїст; англійська комунікативна поведінка; американська комунікативна поведінка